The Adherence-Associated Lipoprotein P100, Encoded by an opp Operon Structure, Functions as the Oligopeptide-Binding Domain OppA of a Putative Oligopeptide Transport System in Mycoplasma hominis - Henrich, Birgit (American Society for Microbiology, 1999)
Mycoplasma hominis, a cell-wall-less prokaryote, was shown to be cytoadherent by the participation of a 100-kDa membrane protein (P100). To identify the gene encoding P100, peptides of P100 were partially sequenced to enable the synthesis of P100-specific oligonucleotides suitable as probes for the detection of the P100 gene. With this strategy, we identified a genomic region of about 10.4 kb in M. hominis FBG carrying the P100 gene. Analysis of the complete deduced protein sequence suggests that P100 is expressed as a pre-lipoprotein with a structure in the N-terminal region common to peptide-binding proteins and an ATP- or GTP-binding P-loop structure in the C-terminal region. Downstream of the P100 gene, an additional four open reading frames putatively encoding the four core domains of an active transport system, OppBCDF, were localized. The organization of the P100 gene and oppBCDF in a transcriptionally active operon structure was demonstrated in Northern blot and reverse transcription-PCR analyses, as all gene-specific probes detected a common RNA of 9.5 kb. Primer extension analysis revealed that the transcriptional initiation site was localized 323 nucleotides upstream of the methionine-encoding ATG of the P100 gene. The peptide-binding character of the P100 protein was confirmed by fluorescence spectroscopy and strongly suggests that the cytoadherence-mediating lipoprotein P100 represents OppA, the substrate-binding domain of a peptide transport system in M. hominis.